2011
DOI: 10.1038/npp.2011.82
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Genetic Profile for Dopamine Signaling Predicts Ventral Striatum Reactivity

Abstract: Research integrating neuroimaging and molecular genetics has yielded important insights into how variability in brain chemistry predicts individual differences in brain function, behavior and related risk for psychopathology. However, existing studies have been limited by their focus on the independent effects of single polymorphisms with modest impact on brain chemistry. Here, we explored the effects of five functional polymorphisms affecting dopamine (DA) signaling on reward-related ventral striatum (VS) rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
239
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(260 citation statements)
references
References 56 publications
18
239
2
1
Order By: Relevance
“…In concordance with our data, two prior reports found that an aggregate of genes provided a stronger account of the neural substrates underlying reward reactivity of the striatum than individual genes (Nikolova et al, 2011;Stice et al, 2012). Despite opposite scoring algorithms employed for DAT1 and DRD4 genotypes in these two studies, both found that ventral striatal reactivity to food or monetary reward varied as a function of a multilocus genetic score.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In concordance with our data, two prior reports found that an aggregate of genes provided a stronger account of the neural substrates underlying reward reactivity of the striatum than individual genes (Nikolova et al, 2011;Stice et al, 2012). Despite opposite scoring algorithms employed for DAT1 and DRD4 genotypes in these two studies, both found that ventral striatal reactivity to food or monetary reward varied as a function of a multilocus genetic score.…”
Section: Discussionsupporting
confidence: 77%
“…Genetic composite scores have been used as an index for dopaminergic activity, and a link between genes involved in dopamine signaling capacity and ventral striatal reactivity to rewards has been demonstrated (Nikolova et al, 2011;Stice et al, 2012). Because neuropsychiatric disorders that feature decisionmaking deficits are associated with dysregulated dopamine function (Frank et al, 2007;Rahman et al, 2001), understanding the link between markers for striatal dopamine activity and neural function in healthy individuals may help select therapeutic targets for pathological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Biffi et al (2010) found that 3% of the variance in MRI-derived volumes of several brain regions could be explained from a number of candidate genes for Alzheimer's disease. Nikolova et al (2011) showed 11% of the variance in ventral striatal reactivity could be explained from their panel of five polymorphisms. We also found that our candidate polymorphisms displayed extensive, significant effects on 82% of the volume of the corpus callosum, when cumulatively modeled at a voxelwise FA basis, which captures more spatial detail than an average measure of FA across the corpus callosum.…”
Section: Discussionmentioning
confidence: 99%
“…Carayol et al (2010), for instance, reported on the cumulative effect of four candidate SNPs on the risk for autism, using a casecontrol approach. These models are beginning to be applied to brain imaging in the context of neuropsychiatric disorders (Biffi et al, 2010;Hibar et al, 2011a;Nikolova et al, 2011), and may provide more biologically meaningful predictions with implications for personalized diagnosis and therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation